A first investigation of accuracy, precision and sensitivity of phase-based x-ray dark-field imaging. (4th November 2016) - Astolfo, Alberto; Endrizzi, Marco; Kallon, Gibril; Millard, Thomas P; Vittoria, Fabio A; Olivo, Alessandro
Abstract: In the last two decades, x-ray phase contrast imaging (XPCI) has attracted attention as a potentially significant improvement over widespread and established x-ray imaging. The key is its capability to access a new physical quantity (the 'phase shift'), which can be complementary to x-ray absorption. One additional advantage of XPCI is its sensitivity to micro structural details through the refraction induced dark-field (DF). While DF is extensively mentioned and used for several applications, predicting the capability of an XPCI system to retrieve DF quantitatively is not straightforward. In this article, we evaluate the impact of different design options and algorithms on DF retrieval for the edge-illumination (EI) XPCI technique. Monte Carlo simulations, supported by experimental data, are used to measure the accuracy, precision and sensitivity of DF retrieval performed with several EI systems based on conventional x-ray sources. The introduced tools are easy to implement, and general enough to assess the DF performance of systems based on alternative (i.e. non-EI) XPCI approaches.